Peroxisome assembly factor 1: nonsense mutation in a peroxisome-deficient Chinese hamster ovary cell mutant and deletion analysis. - Tsukamoto, T (1994)
A cDNA encoding 35-kDa peroxisome assembly factor 1 (PAF-1), a peroxisomal integral membrane protein, was cloned from Chinese hamster ovary (CHO) cells and sequenced. The CHO PAF-1 comprised 304 amino acids, one residue shorter than rat or human PAF-1, and showed high homology to rat and human PAF-1: 90 and 86% at the nucleotide sequence level and 92 and 90% in amino acid sequence, respectively. PAF-1 from these three species contains a conserved cysteine-rich sequence at the C-terminal region which is exactly the same as that of a novel cysteine-rich RING finger motif family. PAF-1 cDNA from a peroxisome-deficient CHO cell mutant, Z65 (T. Tsukamoto, S. Yokota, and Y. Fujiki, J. Cell Biol. 110:651-660, 1990), contained a nonsense mutation at the codon for Trp-114, resulting in premature termination. Truncation in PAF-1 of either 19 amino acids from the N terminus or 92 residues from the C terminus maintained the peroxisome assembly-restoring activity when tested in both the Z65 mutant and the fibroblasts from a Zellweger patient. In contrast, deletion of 27 or 102 residues from the N or C terminus eliminated the activity. PAF-1 is encoded by free polysomal RNA, consistent with a general rule for biogenesis of peroxisomal proteins, including membrane polypeptides, implying the posttranslational transport and integration of PAF-1 into peroxisomal membrane.